Faktor-Faktor yang Mempengaruhi Opini Going Concern - Dewi, Sofia Prima (Akuntansi Krida Wacana, 2011)
Â The purpose of this research is to examines the influence of auditor reputation, financial condition, prior opinion, sales growth, return on asset, debt default, and firm size on a going concern opinion. The data was collected using purposive sampling method. The sample used in this research were 96 observation covering the period from 2006 until 2009. Logistic regression on going concern opinion. On the other hand, auditor reputation, companyâs financial condition, sales growth, return on asset, and firm size has no effect on going concern opinion.Â Keyword : Going Concern Opinion, Auditor Reputation, Financial Condition, Prior Opinion, Sales Growth, Return On Asset, Debt Default, Frim Size.